Side effects of drugs used in cancer chemotherapy - Pylak-Piwko, Oktawia Julia; Nieradko-Iwanicka, Barbara (Journal of Education, Health and Sport, 2017)
Introduction Chemotherapy is a systemic treatment of tumors with use of cytotoxic agents which affect the whole organism destroying cells tumor cells which divide quickly. These medicines damage also healthy tissues of the organism causing some side effects in different systems of organs. Objective The objective of this study is to review the most common side-effects of drugs used in chemotherapy based on the available literature. Methods 22 publications published between 2005-2016 concerning side-effects of drugs used during the chemotherapy of the cancer were analyzed. Results and discussion Majority of the side-effects of chemotherapeutic drugs are symptoms from the digestive tract, bone marrow, cardiovascular system and kidneys. A systematic review of medicines responsible for these symptoms was accomplished. Conclusions Majority of patients treated with chemotherapy experience its’ side effects. The most noticeable ones are those of the digestive tract, like diarrhea or vomiting, which cause considerable discomfort and arouse the urgent need for the doctor’s help. However, the most dangerous effects, which directly threaten a patient’s life are severe cytopenias and unexpected failure of the cardiovascular system.